Analisis Kompetensi Pedagogik Guru dalam Pembelajaran Secara Daring di Madrasah Ibtidaiyah Al Mukhlis Jakarta Barat - Ulfa Oktavianti; Nurul Febrianti (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Muhammadiyah Sukabumi, 2022)
This study aims to determine the pedagogic competence of elementary school teachers in online learning at Madrasah Ibtidaiyah Al Mukhlish. This research was conducted using a qualitative approach with data collection techniques in the form of interviews, observations, and documents. Data analysis followed the Miles and Huberman stages which consisted of three stages: data reduction, data presentation, and drawing conclusions. (in Sugiyono, 2020: 184) the validity tests used by researchers are credibility, transfermability, dependability, conformability. The results of this study indicate that pedagogic competence in curriculum development, educational learning activities, communication with students. The difficulty faced is that the users of learning methods are less varied when learning online at Madrasah Ibtidaiyah Al Mukhlish, West Jakarta.